Timetable planning and scheduling system (TPS) - Koh, Peh Wah. (2012)
A web-based timetable planning system is to be developed to be used for scheduling of time table and staff duty allocation for SCE courses. The program allows manual input of data and scheduling of classes, and provide resource and constraint checking.